De la carte diachronique à la trajectoire géohistorique : modélisation du changement paysager d’un cône torrentiel - Thérèse Hugerot; Laurent Astrade; Christophe Gauchon; Estelle Ployon (M@ppemonde)
Conventional cartographic tools do not allow a landscape trajectory to be formalized other than through a diachronic study. The objective is to propose a geohistorical approach by analyzing the phases of change and their spatialization through the use of a documentary corpus gathered in a GIS. This article presents the case of Saint-Antoine alluvial fan (Northern Alps), whose landscape trajectory, in the form of diachronic maps, transition diagram, ternary plot and heuristic timelines, reveals the trends and rhythms of change (continuity, bifurcation, turning point).